A Simulation of an Income Contingent Tuition Scheme in a Transition Economy - Vodopivec, M. (2012)
The paper takes advantage of exceptionally rich longitudinal data on the universe of labor force participants in Slovenia and simulates the working of an income contingent loan scheme that seeks to recover part of schooling costs. The simulations show that under the base variant (where the target cost recovery rate is 20% and the contribution rate is 2%), 55% of individuals would have repaid their entire debt within 20 years; 19% of individuals still would not have repaid any of their debt after 20 years; and the "leakage" of the scheme due to uncollected debt would have been 13.5% of total lending. By piggybacking on existing administrative systems, implementation costs would be minimal, amounting to less than 0.5% of collected debt.